Whitewashing America : material culture and race in the antebellum imagination - Heneghan, Bridget T. (University Press of Mississippi, 2003)
Literary criticism -- American history --> Even before mass marketing, American consumers bought products that gentrified their households and broadcast their sense of "the good things in life." Bridging literary scholarship, archaeology, history, and art history, Whitewashing America: Material Culture and Race in the Antebellum Imagination explores how material goods shaped antebellum notions of race, class, gender, and purity. From the Revolutionary War until the Civil War, American consumers increasingly sought white-colored goods. Whites preferred mass-produced and specialized produc